The Role of Chaebol in econiomic recovey of south Korea from 2008 global Financial crisis - Anis Abdillah (HI 13 UMY 105, 2013)
The case of the 2008 global financial crisis caused by the subprime mortgage crisis and several investment banks collapse. The financial crisis spreads over the world rapidly and creates bad impact for many countries in the world especially for the country that relies on the export and import activity. For example is South Korea. As the impact of the 2008 global financial crisis, the GDP of South Korea decreased. GDP growth rate in 2007 was 1.4%, GDP in 2008 was 0.3%, GDP of the last 2008 was -0.1% and in the early of 2009 GDP growth rate was -4.5%. The other impact is some companies are in alert. Even though the impact of the 2008 global crisis significantly deteriorates the economic condition of South Korea, there were also important achievements of South Korea. The achievements are the GDP from the end of 2009 to 2010. South Korea's nominal GDP in 2010 was estimated at between 1.1 and 1.2 trillion dollars. Export achieved to 28.3% and import achieved to 31.6% in 2010. Those facts show that South Korea is one country that survive and succeed in its recovery. It requires the important role of actor economy. One important actor of South Korea economy is Chaebol. Finally, this undergraduate thesis discusses about the role of Chaebol in economic recovery of South Korea. The Chaebol involves in economic policy and it contributes in development of economy of South Korea. Furthermore, the writer tends explore and analyze the issue based on the theory of developmental state, interest group and the concept of economic recovery. Key Word: Chaebol, global financial crisis, interest group, Chaebol, economic recovery.